2005
DOI: 10.1152/ajplung.00455.2004
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hypoxia elevates intracellular pH and activates Na+/H+exchange in pulmonary arterial smooth muscle cells

Abstract: (CH), caused by many lung diseases, results in pulmonary hypertension due, in part, to increased muscularity of small pulmonary vessels. Pulmonary arterial smooth muscle cell (PASMC) proliferation in response to growth factors requires increased intracellular pH (pH i) mediated by activation of Na ϩ /H ϩ exchange (NHE); however, the effect of CH on PASMC pH i homeostasis is unknown. Thus we measured basal pH i and NHE activity and expression in PASMCs isolated from mice exposed to normoxia or CH (3 wk/10% O 2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
118
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(130 citation statements)
references
References 42 publications
(67 reference statements)
10
118
2
Order By: Relevance
“…We previously reported on the inhibitory effect of reduced NHE activity in the proliferation of PASMCs (6) and on chronic hypoxia-induced pulmonary hypertension and vascular remodeling (7). Increased expression of the NHE1 gene was evident in animals with hypoxia-induced pulmonary hypertension and vascular remodeling (6)(7)(8)(9)(10). Moreover, we recently found that deficiency of the NHE1 gene prevented hypoxia-induced pulmonary hypertension and vascular remodeling in mice (11), accompanied by a significantly reduced proliferation of PASMCs and decreased medial wall thickness of the pulmonary arteries.…”
mentioning
confidence: 99%
“…We previously reported on the inhibitory effect of reduced NHE activity in the proliferation of PASMCs (6) and on chronic hypoxia-induced pulmonary hypertension and vascular remodeling (7). Increased expression of the NHE1 gene was evident in animals with hypoxia-induced pulmonary hypertension and vascular remodeling (6)(7)(8)(9)(10). Moreover, we recently found that deficiency of the NHE1 gene prevented hypoxia-induced pulmonary hypertension and vascular remodeling in mice (11), accompanied by a significantly reduced proliferation of PASMCs and decreased medial wall thickness of the pulmonary arteries.…”
mentioning
confidence: 99%
“…Initial studies demonstrated that PASMCs isolated from chronically hypoxic mice, a widely used model of hypoxic PH, exhibited an alkaline shift in resting pH i that continued to be evident days after the cells had been removed from the animals and the hypoxic stimulus. 27 That the elevation in basal pH i was still observed when the cells were perfused with HCO 3 − -free buffer and could be significantly reduced by addition of an NHE inhibitor was consistent with NHE mediating the hypoxia-induced alkaline shift in pH i . Moreover, the elevation of pH i in PASMCs isolated from chronically hypoxic mice was correlated with augmented NHE activity.…”
Section: Role Of Nhe1 In Acute Hypoxic Pulmonary Vasoconstriction (Hpv)mentioning
confidence: 54%
“…20,22,23 In contrast to the relatively wide distribution of expression seen with other NHE isoforms, NHEs 6-10 have significantly more restricted tissue and/or intracellular localization. 15,[24][25][26] Examination of the best-characterized NHEs revealed that NHE1, but not NHE2 or NHE3, was present in mouse 27 and rat 28 PASMCs, indicating that NHE1 is the primary isoform responsible for regulating cytosolic pH in this cell type.…”
Section: The Nhe Isoformsmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of NHE-1 has been shown to be a pivotal event in cell damage induced by ischemia and reperfusion in the brain (Horikawa et al, 2001;Hwang et al, 2008;Luo et al, 2005), heart (Liu et al, 1997;Murphy et al, 1991;Wang et al, 2003), liver (Gores et al, 1989), and lungs (Rios et al, 2005). Here we will review recent findings implicating NHE-1 activation as a critical event in the pathogenesis of cellular dysfunction after cerebral ischemia, and the growing evidence supporting the use of NHE inhibitors as neuroprotective agents following cerebral ischemia.…”
mentioning
confidence: 97%